Mobile-phone-based e-diary derived patient reported outcomes: Association with clinical disease activity, psychological status and quality of life of patients with multiple sclerosis. - Daniel Golan; Smadar Sagiv; Lea Glass-Marmor; Ariel Miller (PLoS ONE)
Background The applicability of mobile digital technology to promote clinical care of people with multiple sclerosis (pwMS) is gaining increased interest as part of the implementation of patient-centered approaches. We aimed at assessing adherence to a smartphone-based e-diary, which was designed to collect patient-reported outcomes (PROs). Secondary objectives were to evaluate the construct and predictive validity of e-diary derived PROs and to explore the various factors that were associated with changes in PROs over time. Materials and methods In this observational cohort study patients downloaded an MS tailored e-diary into their personal smartphones. Report of PROs was enquired once monthly for a period of one year through a smartphone-based application, using previously validated tools. An e-diary derived bodily function summary score (eBF) was defined as the sum of scores depicting vision, limbs function, pain, bowl/ bladder dysfunction, pseudobulbar affect and spasticity. Multiple linear regression and analysis of covariance were used to determine the association between PROs, clinician-reported outcomes (ClinROs) of disease activity and quality of life (QoL). Regression coefficient analysis was used to compare the slope of change in eBF before and after a relapse. Results 97 pwMS downloaded the e-diary [Female: 64 (66%), EDSS 3.4±2.1]. 76 patients (78%) completed the 12-month study period. 53 patients (55%) submitted ≥75% of requested surveys. Anxiety was negatively associated with adherence to periodic PROs assessments by the e-diary. E-diary derived PROs were significantly correlated with corresponding functional system scores (0.38< r <0.8, P<0.001). eBF score significantly predicted QoL (β = -0.36, P = 0.001) while EDSS did not. Change in eBF score over time was independently associated with the occurrence of an MS relapse (F = 4.4, P = 0.04), anxiety (F = 6.4, P = 0.01) and depression (F = 5.1, P = 0.03). Individual regression slopes of eBF scores were significantly higher pre-relapse than post-relapse (3.0±3.3 vs. -0.8±2.0, P = 0.007). Conclusion Adherence of pwMS to recording in an e-diary collecting PROs was high. Changes in e-diary derived PROs over time predict clinical MS relapses on the group level and thus carry the potential of usage in clinical research as well as for improved MS care in real world setting.